VALIDATION CONTROL IN FINITE ELEMENT ANALYSIS OF WIDE BEAM-COLUMN CONNECTIONS USING CONCRETE DAMAGE PLASTICITY UNDER CYCLIC LOADING - Putu Ayu Priska Dewi; I Ketut Sudarsana; I Gede Adi Susila (Journal of Infrastructure Planning and Engineering, 2025)
This study investigates the validation of a finite element model for exterior wide beam–column connections using the Concrete Damage Plasticity (CDP) approach under reversed cyclic loading. The research focuses on identifying optimal CDP parameters—mesh size, dilation angle, and viscosity—through a structured trial-and-error process to enhance simulation accuracy. Using the SPWWS specimen as a benchmark, the final model configuration (40 mm mesh, 40° dilation angle, and 0.005 viscosity) produced peak load errors of 3.47% (positive) and 8.73% (negative) compared to experimental data. The simulation also replicated key damage mechanisms including diagonal, flexural, and torsional cracking observed in the laboratory test. These results validate the effectiveness of the calibrated CDP model in capturing both global and local nonlinear behaviors of RC joints under seismic loading. The validated model offers a reliable basis for future studies on reinforced concrete joints under modified loading conditions or strengthening interventions.